Numerical Simulation of UWB Electromagnetic Pulses Propagation in Dispersive Electrodynamic Lines - Gritsunov, A. V.; Ostapyuk, N. V. (My University, 2007)
This paper considers a computer simulation method for ultrawideband (UWB) pulse fields excited in a regular electrodynamic line by either a short external current or by a bunched electron beam. The high-frequency components of the radio pulse move more rapidly than the low-frequency ones, the first overtake the latter after some time. The delay line does not transmit the low-frequency components of the video pulse at all, so this turns into a radio pulse gradually passing some distance.
Keywords: ultrawideband pulse; regular electrodynamic line; dispersion characteristic